Do Expected Shifts in Inflation Affect Estimates of the Long-Run Fisher Relation? - Evans, Martin D. D.; Lewis, Karen K. (Journal of Finance, 1995)
Recent empirical studies suggest that nominal interest rates and expected inflation do not move together one-for-one in the long run, a finding at odds with many theoretical models. This article shows that these results can be deceptive when the process followed by inflation shifts infrequently. The authors characterize the shifts in inflation by a Markov switching model. Based upon this model's forecasts, they reexamine the long-run relationship between nominal interest rates and inflation. Interestingly, the authors are unable to reject the hypothesis that, in the long run, nominal interest rates reflect expected inflation one-for-one. Copyright 1995 by American Finance Association.